HEDGES USED IN THE CONVERSATION BETWEEN BARRACK OBAMA AND BILL CLINTON AT CLINTON GLOBAL INITIATIVE - ARIFIANTO, ZULFIKAR (Language Horizon: Journal of Language Studies, 2014)
Dalam kajian ini akan menganalisa tentang ekspresi hedges, karena fenomena hedges adalah salah satu fitur dari pragmatik lunguistik yang biasa digunakan oleh orang-orang dalam komunikasi sehari-hari. Ekspresi hedges adalah ekspresi yang menunjukkan keraguan atau ketidakpastian penutur terhadap sesuatu yang diucapakan. Sepertihalnya dalam ucapan “Saya rasa mungkin sebaiknya anda membertimbangkan mengenai ini”. Ekspresi saya rasa,mungkin, sebaiknya, dan mempertimbangkan itulah yang disebut sebagai ekspresi hedges. Seluruh ekspresi tersebut menandakan keraguan atau sesuatu yang masih belum pasti. Orang mungkin mempunyai tujuan tertentu dalam menggnakan hedeges di percakapan mereka. Menurut Salager-Meyer dalam Miller(2005) ekspresi hedges mempunyai beberapa jenis, seperti modal auxiliary verbs; modal lexical verbs; introductory phrases; adjectival, adverbial, and nominal modal phrarses; approximator of degree, quantity, frequency, and time;if clauses dan compund hedges. Dismaping itu, hedges juga memiliki beberapa fungsi seperti, minimize the threat to face;ways of being more precise, politeness strategy, juga establish a writing style. Dalam kajian inipenulis bertujuan untuk mencari tahu ekspresi hedges seperti apa beserta fungsinya yang digunakan dalam percakapan antara president Barrack Obama dan mantan President Bill Clinton. Kajian ini menggunakan metode kualitatif dan hanya fokus dalam menganalisa pengguanaan hedges dalam percakapan pada acara Clinton Global Initiative. Speech act digunakan untuk mengidentifikasi maksud dan fungsi hedges yang digunakan dalam ucapan penutur. Dalam kajian ini menjukkan bahwa, jenis hedges yang diguanakan oleh kedua penutur dalam percakapan adalah modal auxiiary verbs; adjectival,adverbial and nominal modal pharses, approximator of degree, quantity, frequency, and time; introductory phrases, if clauses, dan compound hedges. Sementara fungsinya adalah minimize the threat to face; ways of being more precise; dan sebagai a politeness strategy. Dimungkinkan juga bahwa dalam setiasp fungsi dapat berisikan beberapa jenis hedges. Kata kunci:Hedges, types of hedges,Jenis hedges yang digunakan oleh Barrack Obama dan Bill Clinton Abstract This study will analyse t hedges expressions, because the phenomena of hedges are commonly used by the people in their daily communication. Hedges expressions are kind of expressions which are showing a doubtness or an uncertainty of the speaker towards a propostiton they uttered. For instance in this utterance “I think maybe you should consider about it”. The expressions I think, maybe, should, and consider are what is called as hedges expressions. All of those expressions denote a douaboubtness or something which is still uncertain. People may have a certain purposes in using hegdes within their speech. According to Francoise Salager-Meyer in Miller (2005) Hedges expressions have several types, they are modal auxiliary verbs; modal lexical verbs, adjectival, adverbial and nominal modal phrases; approximators of degree, quantity, frequency, and time; introductory phrases; “If” clauses; and compound hedges. Besides, it has also some functions like minimize the threat to face; ways of being more precise; as a politeness strategy; also to establish a writing style. This research tries to find what kind of hedges and the functions used in the conversation between President of the United States, Barrack Obama and the former President Bill Clinton. This research use a qualitative method and only focus in analysing the use of hedges in a conversation at Clinton Global Initiative event. In this research, the speech act used to facilitate in finding and identifying what kind of speech act used in order to know the intention and the function of the utterances. Here, the result of the study is that the hedges types used in the conversation are modal auxiliary verbs; adjectival, adverbial and nominal modal phrases; approximators of degree, quantity, frequency, and time; introductory phrases; “If” clauses; and compound hedges. It can also beesen that there is an exprerssion of adjectival, adverbial and nominal modal phrases, and that expression used by Obama while there is no such expression found in Clinton’s speech.While the functions are minimize the threat to face; ways of being more precise; and as a politeness strategy. It also possible that in each of the functions contain some of hedges types. Keywords: Hedges, forms of hedges, Kind of hedges used by Barrack Obama and Bill Clinton